2019
DOI: 10.5198/jtlu.2019.1512
|View full text |Cite
|
Sign up to set email alerts
|

Complete streets state laws & provisions: An analysis of legislative content and the state policy landscape, 1972–2018

Abstract: Across the U.S., states have adopted Complete Streets legislative statutes—state laws that direct transportation agencies to routinely design and operate roadways to provide safe access for all users, including pedestrians, bicyclists, motorists, and public transit users. To date, there has not been a systematic and comprehensive analysis of the content and provisions of these laws. In this study, Complete Streets state statutes were identified using legal research databases. Using established legal mapping me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…47 Legal mapping, which tracks the prevalence and key elements of laws, addresses this need to generate readily accessible information about the status of the law (and legal trends if undertaken longitudinally). 47 Detailed coding of attributes in laws makes it easier to identify differences (across jurisdictions or over time) and facilitate further research to investigate how these may be connected to PA 12 and other outcomes, such as economic disparities in active travel. 12,34 Legal mapping is, therefore, an important first step toward not only determining how laws can improve PA in populations 48 but also identifying any unintended adverse effects (eg, displacement due to gentrification; poorer sense of community or neighborhood satisfaction).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Legal mapping, which tracks the prevalence and key elements of laws, addresses this need to generate readily accessible information about the status of the law (and legal trends if undertaken longitudinally). 47 Detailed coding of attributes in laws makes it easier to identify differences (across jurisdictions or over time) and facilitate further research to investigate how these may be connected to PA 12 and other outcomes, such as economic disparities in active travel. 12,34 Legal mapping is, therefore, an important first step toward not only determining how laws can improve PA in populations 48 but also identifying any unintended adverse effects (eg, displacement due to gentrification; poorer sense of community or neighborhood satisfaction).…”
Section: Discussionmentioning
confidence: 99%
“…11 There has been research focused on selected areas of lawmaking, such as planning statutes affecting the built environment and PA as well as transportation laws governing the planning of infrastructure that enables safe mobility (including walking and cycling) by road users. 12,13 Other PA-specific examples of research include studies of the impact of state laws governing physical education in high schools on levels of attendance in these classes 14 and the uptake of laws mandating policies in child care services regarding PA, outdoor play, and screen time by children. 15 Although limited in number, these studies illustrate the diversity in the types and levels of laws that are relevant to PA as well as the potential forms of public health law research that can inform the more effective use of these instruments.…”
mentioning
confidence: 99%
“…With respect to transportation system performance, Complete Streets advocates can point to the effectiveness of individual elements of multi-modal transportation design, such as the safety benefits of speed reductions, but the total effect of the Complete Streets framework has been challenging to quantify (Jordan and Ivey 2021; Hui et al 2017; Gregg and Hess 2019; Lenker, Maisel and Ranahan 2016). A few studies of the Complete Streets framework in-action have found a positive effect on pedestrian safety and no effect on residential property values (Porter et al 1972; Schneider 2018; Vandegrift and Zanoni 2018). A review of the equity-focused research on active transportation interventions found that most studies have been cross-sectional, though some longitudinal studies have found weak evidence that the interventions have positive benefits for historically underserved groups by race, ethnicity, and socioeconomic status (Hansmann, Grabow and McAndrews 2022).…”
Section: Complete Streetsmentioning
confidence: 99%
“…55 One legal epidemiology assessment identified 21 Complete Streets state laws across 18 jurisdictions, highlighting their substantive commonalities and identifying policy challenges, such as implementation and evaluation. 55 It further applied evaluation data to these findings, determining, for example, that Florida's 1984 state law "was associated with a 29-year decrease in pedestrian deaths" across the state. 55(p631) Other recent legal epidemiology research has examined a broad range of state laws concerning fair housing, predatory lending, voting rights, and minimum wage laws, among others that altogether implicate structural racism 53 ; telehealth and broadband statutes and regulations 56 ; and the nature, scope, and reach of Health in All Policies.…”
Section: Law and Its Effects Can Be Studied To Expand And Strengthen ...mentioning
confidence: 99%